Pengaruh Konsumsi Teh Hijau Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi - Andini Pramesti Ningrum; Winda Trijayanthi Utama; Intanri Kurniati (CV. Jasa Sukses Abadi, 2021)
Hypertension is one of the most common diseases found in primary medical practice. The manifestation of hypertension is a disorder of cardiovascular hemodynamic balance which has an increase in systolic blood pressure ≥ 140 mmHg and or diastolic blood pressure ≥ 90 mmHg which is persistent, on repeated examinations. Hypertension complications can affect various target organs such as the heart, brain, kidneys, eyes, and peripheral arteries. Hypertension is influenced by the role of intravascular volume, the role of autonomic nerve control, and the role of renin angiotensin aldosterone. Tea is thought to have a variety of health benefits and most of the evidence suggests that green tea consumption is associated with lowering blood pressure. Tea and its secondary metabolites, namely polyphenolic compounds called flavonoid, play an important roles in relaxing smooth muscle contraction, enhancing eNOS activity, reducing vascular inflammation, inhibiting rennin and endothelin-1 activity and anti-vascular oxidative stress. Consumption of green tea can significantly reduce systolic blood pressure by 1.98 mmHg and diastolic blood pressure by 1.92 mmHg. The positive effect of green tea on blood pressure was obtained after consuming low doses (<582.8 mg/day) with long-term duration (≥12 weeks). A drop in blood pressure can lower the chance of complications.